(untitled) (Praxis Educativa, 2023)
This text presents the study of a particular case in which the author shares the narrative of a teaching practice, that is to say, the conjectural script (Bombini, 2002) of a literature class. The procedural framework illustrates how in class students practice the production of texts-readings (Barthes, 1970) based on the novel The Old Man and the Sea by Ernest Hemingway. The objectives of this work were to make this class known, to report a specific practice, to discuss what is read, how and from which position the reading is done, as well as to enhance the horizons of teaching intervention that allows for delivery development (Gerbaudo, 2011) and stimulates discussions about reading.